2016
DOI: 10.1016/j.neuron.2016.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Receptor NR1H3 in Familial Multiple Sclerosis

Abstract: SUMMARYMultiple sclerosis (MS) is an inflammatory disease characterized by myelin loss and neuronal dysfunction. Despite the aggregation observed in some families, pathogenic mutations have remained elusive. In this study we describe the identification of NR1H3 p.Arg415Gln in seven MS patients from two multi-incident families presenting severe and progressive disease, with an average age at onset of 34 years. Additionally, association analysis of common variants in NR1H3 identified rs2279238 conferring a 1.35-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…A). The pattern of disease inheritance in this family is suggestive of an autosomal‐dominant trait with reduced penetrance; therefore, only rare heterozygote coding substitutions identified in all affected individuals were considered potentially pathogenic; detailed methodology has been previously described (Wang et al., ). Exome analysis identified a total of 82,073 variants across all five affected subjects, with 3,548 autosomal heterozygote genotypes being observed in all family members examined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A). The pattern of disease inheritance in this family is suggestive of an autosomal‐dominant trait with reduced penetrance; therefore, only rare heterozygote coding substitutions identified in all affected individuals were considered potentially pathogenic; detailed methodology has been previously described (Wang et al., ). Exome analysis identified a total of 82,073 variants across all five affected subjects, with 3,548 autosomal heterozygote genotypes being observed in all family members examined.…”
Section: Resultsmentioning
confidence: 99%
“…Two‐point logarithm of odds (LOD) score was obtained with MLINK assuming a dominant model, with a fully penetrant mutation and without phenocopies, as previously described (Chartier‐Harlin et al., ; Ott, ; Wang et al., ). The deleterious allele was defined with a 0.0001 frequency, and the marker‐allele frequencies were determined empirically from genotyped individuals within the family.…”
Section: Methodsmentioning
confidence: 99%
“…In MS, as in most other neurodegenerative diseases, genetic influences play an important role as well. However, unlike in a number of other neurodegenerative disorders, where specific mutations have been identified as causes for at least a subset of these, such mutations have yet to be identified in MS 1820 . Instead, a large number of susceptibility loci, the vast majority of which are related to immune function, have been found through genome-wide association studies (GWASs) 2027 .…”
Section: The Genetics Of Msmentioning
confidence: 99%
“…Recently, Wang et al. reported that they discovered the NR1H3 p.Arg415Gln mutation in seven MS patients from two multi‐case families with severe and progressive disease course, and concluded that it is the first pathogenic mutation for MS . However, the finding was not replicated in the datasets of the International MS Genetics Consortium with a 13‐fold larger sample size .…”
Section: What Is Next For Ms Genetics?mentioning
confidence: 99%